Die Europäische Währungsunion im Treibsand: Fehlende Lohnkoordination und fiskalische Schwächen gefährden das europäische Projekt - Heine, Michael; Herr, Hansjörg (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
In the European Monetary Union (EMU) development of unit-labour costs and inflation rates differs substantially among regions. This shows that the different wage determination models in the EMU did not converge to create a EMU-wide coherent wage bargaining system. The result are huge regional imbalances. Germany the biggest economy and the country with the lowest increase in unit-labour costs in EMU already realises big and increasing current account surpluses against other EMU countries. Spain, Italy or Portugal suffer from big current account deficits. The financial power of the European centre is too limited to prevent increasing regional problems. What is needed in Europe is a deeper institutional and political integration to combine functional monetary, fiscal, wage and regional policies.